Investigation into the role of endogenous abscisic acid during ripening of imported avocado cv. Hass - Meyer, Marjolaine D.; Chope, Gemma A.; Terry, Leon A. (Wiley, 2017)
BACKGROUND The importance of ethylene in avocado ripening has been extensively studied. In contrast, little is known about the possible role of abscisic acid (ABA). The present work studied the effect of 1-methylcyclopropene (1-MCP) (0.3 μL L−1), e+® Ethylene Remover and the combination thereof on the quality of imported avocado cv. Hass fruit stored for 7 days at 12 °C. Ethylene production, respiration, firmness, colour, heptose (C7) sugars and ABA concentrations in mesocarp tissue were measured throughout storage. RESULTS Treatment with e+® Ethylene Remover reduced ethylene production, respiration rate and physiological ripening compared with controls. Fruit treated with 1-MCP + e+® Ethylene Remover and, to a lesser extent 1-MCP alone, had the lowest ethylene production and respiration rate and hence the best quality. Major sugars measured in mesocarp tissue were mannoheptulose and perseitol, and their content was not correlated with ripening parameters. Mesocarp ABA concentration, as determined by mass spectrometry, increased as fruit ripened and was negatively correlated with fruit firmness. CONCLUSIONS Results suggest a relationship between ABA and ethylene metabolism since blocking ethylene, and to a larger extent blocking and removing ethylene, resulted in lower ABA concentrations. Whether ABA influences avocado fruit ripening needs to be determined in future research. © 2017 Society of Chemical Industry
Keywords: e+® Ethylene Remover; 1-MCP; imported avocado; C7 sugars; abscisic acid